2021
DOI: 10.24018/ejfood.2021.3.6.406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Nutrient Management on Okra Production in Acid Soil

Abstract: Integrated Nutrient Management (INM) is a novel strategy to achieve sustainable crop production in degraded soils through judicious and balanced plant nutrients utilization. Sole application of chemical fertilizers in crop production causes soil and environmental pollution. The present study was designed to assess the effects of application of organic manures conjointly with chemical fertilizers on growth and yield of okra in acid soil. The experiment was consisted of four treatments viz. T0 [Control], T1 [Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…For the yield parameters, the applied fertilizers produced a highly significant effect on all the parameters studied. The treatment of 50% of mineral fertilizers with cation balance+½ poultry manure produced the highest values for the productivity parameters, which corroborates with the work of [33] on okra. This performance is due to the benefic actions of organic and mineral fertilizers with cation balance on acidic soils [34].…”
Section: Discussionsupporting
confidence: 86%
“…For the yield parameters, the applied fertilizers produced a highly significant effect on all the parameters studied. The treatment of 50% of mineral fertilizers with cation balance+½ poultry manure produced the highest values for the productivity parameters, which corroborates with the work of [33] on okra. This performance is due to the benefic actions of organic and mineral fertilizers with cation balance on acidic soils [34].…”
Section: Discussionsupporting
confidence: 86%
“…A similar kind of result having maximum stem diameter in chili was obtained by M.R., (2016) [5] . Also, Singh et al, (2012) [29] and (Binte et al, 2021) [25] observed a progressive growth in the stem diameter of okra plants when organic fertilizers combined with inorganic fertilizers were used in acidic soil. Results from Table 5 revealed that even the different levels of organic and inorganic fertilizers did not significantly influence the leaf numbers.…”
Section: Discussionmentioning
confidence: 99%